2014
DOI: 10.1038/icb.2014.88
|View full text |Cite
|
Sign up to set email alerts
|

Roles of autophagy in HIV infection

Abstract: Autophagy is a major cellular pathway, which at basal levels regulates and maintains the cytoplasmic environment through the capture, isolation and digestion of intracellular materials in a specialized structure called an autophagosome. The unique ability of autophagy to degrade large targets, such as damaged and surplus organelles, intracellular microbes and protein aggregates, has made it a prime focus in inflammation and microbial research. Indeed, autophagy has been shown to be involved in a number of infe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
57
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(57 citation statements)
references
References 86 publications
(135 reference statements)
0
57
0
Order By: Relevance
“…Separate reviews on this topic have appeared, and the interested reader is directed to an excellent recent article for a much more detailed analysis. (Dinkins et al, 2014) However, a brief survey of the HIV-autophagy literature is informative with respect to the very different relationships viruses and autophagy have depending on the cellular context.…”
Section: The Complex Relationship Between Hiv and Autophagymentioning
confidence: 99%
“…Separate reviews on this topic have appeared, and the interested reader is directed to an excellent recent article for a much more detailed analysis. (Dinkins et al, 2014) However, a brief survey of the HIV-autophagy literature is informative with respect to the very different relationships viruses and autophagy have depending on the cellular context.…”
Section: The Complex Relationship Between Hiv and Autophagymentioning
confidence: 99%
“…Autophagosomes play a vital role in HIV-1 biogenesis (51,52). In macrophages, autophagy is stimulated by HIV-1 through the TLR8 signaling that occurs at early stages of infection, while during chronic infection, autophagy is inhibited.…”
Section: Methodsmentioning
confidence: 99%
“…Beclin1 can act as a positive regulator of autophagy and confers specificity to the phosphatidylinositol-3 kinase -Vps34-Atg14 complex, which is essential for autophagosome formation, and by interacting with the anti-apoptotic protein Bcl2, autophagy is inhibited (Parzych and Klionsky, 2014). In the last decade, numerous evidence has shown that autophagy is a critical target for HIV during the viral life cycle which has led to an increasing effort to understand the role of autophagy in those cells affected by HIV infection (Dinkins et al, 2015). …”
Section: Introductionmentioning
confidence: 99%